Analisis Data Sekunder Kecelakaan Kerja di Wilayah Kerja BPJS Ketenagakerjaan Cabang Meulaboh Pada Pekerja di PT. X Kabupaten Aceh Singkil Tahun 2025 - Resa Sri Wahyuni; Wintah Wintah; Siti Maisyaroh Fitri Siregar; Zakiyuddin Zakiyuddin; Pesona Dessritina (Universitas Pahlawan Tuanku Tambusai, 2026)
Occupational accidents are unforeseen events that generally occur beyond operational predictions. This study aims to identify and analyze various factors associated with the incidence of workplace accidents among participants of the BPJS Ketenagakerjaan Meulaboh Branch throughout 2025. A quantitative method with a cross-sectional design was applied. The study population comprised all 154 workers who filed claims for Work Accident Insurance (JKK). Using a purposive sampling technique, the sample was focused on the region with the highest case prevalence among the eight regencies under the BPJS working area, yielding 50 specific cases at PT. X in Aceh Singkil Regency. The data source relied entirely on secondary data from JKK claim reports for the 2025 period. Characteristics of age, length of service, accident type, time of occurrence, incident location, along with aspects of unsafe actions and unsafe conditions were analyzed using a univariate approach, while the bivariate hypothesis was tested using fisher's exact test. Statistical analysis demonstrated a significant association between workplace accidents and accident location (p=0.039), unsafe actions (p=0.022), and physical work environment conditions (p=0.000). Conversely, no significant correlation was found for age (p=0.597), length of service (p=0.224), or time of the accident (p=0.233). This study concludes that spatial/location factors, behavioral deviations from safety protocols, and sub-standard environmental conditions are closely linked to workplace accidents at PT. X, Aceh Singkil Regency, in 2025. It is recommended that the company tighten the implementation of the Occupational Safety and Health Management System (SMK3), supported by technical education programs and routine OSH supervision to mitigate operational risks.